1998
DOI: 10.1897/1551-5028(1998)017<2185:efdeot>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Differential Effects of 2,4,6-Trinitrotoluene and Other Munitions Compounds on Specific Subpopulations of Soil Microbial Communities

Abstract: The effects of 2,4,6-trinitrotoluene (TNT) and other munitions compounds on indigenous microbial communities in several soils were examined. Culturable heterotrophs, concentrations of phospholipid fatty acid (PLFA), and basal respiration rates exhibited slight negative correlations with high TNT and 1,3,5-trinitrobenzene (TNB) levels. Heat-shock-resistant culturable heterotrophs, percentage of gram-positive soil isolates, mole percent of branched PLFA, and 10Me18:0 (tuberculostearic acid) were observed to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
38
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 29 publications
11
38
1
1
Order By: Relevance
“…Supporting our results, several investigators have found that TNT has a much higher toxicity than dinitrotoluenes or the mono-amino metabolites [31,[40][41][42]. Although TNB has a higher toxicity to soil microbes than does TNT [10], TNB was detected in only 27 of 54 samples (11 samples in the dead zones and 16 in the surrounding areas), and its level was always lower than 87 mg/ kg. Unlike the observations of Fuller and Manning [10], no significant correlation was found between TNB levels and microbial activities in our field soils.…”
Section: Field Studysupporting
confidence: 89%
See 4 more Smart Citations
“…Supporting our results, several investigators have found that TNT has a much higher toxicity than dinitrotoluenes or the mono-amino metabolites [31,[40][41][42]. Although TNB has a higher toxicity to soil microbes than does TNT [10], TNB was detected in only 27 of 54 samples (11 samples in the dead zones and 16 in the surrounding areas), and its level was always lower than 87 mg/ kg. Unlike the observations of Fuller and Manning [10], no significant correlation was found between TNB levels and microbial activities in our field soils.…”
Section: Field Studysupporting
confidence: 89%
“…In addition, TNT is cytotoxic and genotoxic to bacterial and mammalian cells [6][7][8]. These laboratory results are supported by two field studies that reported TNT toxicity to cucumber, radish, earthworm, Photobacterium phosphoreum [9], and soil microbial communities [10]. However, most of the studies assessing TNT toxicity are short-term acute assays that use aquatic or terrestrial species not often found at contaminated sites.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations